Are we missing dementia with Lewy bodies?: a case report. (August 2018) - Wearne, Deborah; Genetti, Amanda; Restifo, Sam; Harriss, Alina
Objectives: We aim to explore the importance of early diagnosis of dementia with Lewy bodies in order to facilitate effective psychiatric management. We present a case where delayed diagnosis stemming from an atypical presentation illustrates the complex issues involved in identifying and treating this type of dementia. Conclusions: We discuss the difficulty of diagnosis of this disorder in the absence of obvious memory dysfunction or parkinsonian symptoms. We use the case to draw attention to the limited availability of certain investigations and treatment options in Australia.